Fox in socks ebook - Dr. Seuss (Classic Seuss., 2014)
NATIONAL BESTSELLER • Kids will love learning how wacky words can be with this classic picture book of tongue twisters from Dr. Seuss! “This is a book you READ ALOUD to find out just how smart your tongue is. The first time you read it, don’t go fast! This Fox is a tricky fox. He’ll try to get your tongue in trouble.” When a fox in socks meets Knox in a box, you know that hilarity will ensue! Add chicks with bricks (and blocks and clocks) and you’re sure to get your words twisted and lips locked. With his unmistakable gift for rhyme, Dr. Seuss creates a fun way for beginning readers to dive into the joy of reading. Beginner Books are fun, funny, and easy to read! Launched by Dr. Seuss in 1957 with the publication of The Cat in the Hat , this beloved early reader series motivates children to read on their own by using simple words with illustrations that give clues to their meaning. Featuring a combination of kid appeal, supportive vocabulary, and bright, cheerful art, Beginner Books will encourage a love of reading in children ages 3–7.